Hydroxyapatite and tricalcium phosphate composites with bioactive glass as second phase: State of the art and current applications. Issue 4 (23rd December 2015) - Bellucci, Devis; Sola, Antonella; Cannillo, Valeria
Abstract: Calcium phosphates are among the most common biomaterials employed in orthopaedic and dental surgery. The efficacy of such systems as bone substitutes and bioactive coatings on metallic prostheses has been proved by several clinical studies. Among these materials, hydroxyapatite (HA) and tricalcium phosphate (TCP) play a prominent role in medical practice since the '80s. In the last years, numerous attempts to combine HA or TCP with bioactive glasses have been made. There are two main motivations for sintering calcium phosphates with a glassy phase: on the one hand, it is possible to tune the dissolution of the final system and to enhance its biological response through the synergistic combination of two bioactive phases; on the other hand, the glass acts as a sintering aid with the aim to increase the densification of the composite and thus its mechanical strength. In this sense, TCP and HA are penalized by their relatively poor fracture toughness and tensile strength compared to natural bone, which makes it impossible to use them in load‐bearing applications. Moreover, the bioactivity index of pure calcium phosphates is typically lower with respect to that of many bioactive glasses. In this review, the state of the art and current applications of composites, based on HA or TCP with bioactive glass as second phase, are presented and discussed. A special emphasis is given to the processing and mechanical behaviour of these systems, together with their biological implications, as a function of the composition of the glass employed as second phase. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 1030–1056, 2016.